Analisis Komparatif Pertumbuhan Pendapatan Daerah Di Lima Wilayah Adat Tahun 2012-2018 Provinsi Papua - Rachmaeny Indahyani; Robert M. WST. Marbun (Universitas Cenderawasih, 2020)
This research generally have aims to analisys income growth comparative in five customary territory since 2021 – 2018 at Papua Province. Data be used in secondary data, The method be used to analysis with make discreption kualitatif and finaly the output analysis will be kuantitatif, The result of analysis is 1) the research found different level of independence between region it’s mean inequality in independency. This attention for government Provinsi to take policy for equality in five customary territory 2) Approach strategy or policy of developmend regional in five customary territory is depend on actor in implementation decession maker, komitmen, for to the aims of policy.Keywords: growth, comparative income, five customary territory, Papua